CSR and Reporting by Selected Indian Companies: An Exploration - Bhalla, Rajni (Prabandhan: Indian Journal of Management, 2013)
CSR has become popular all over the globe. In the developing countries like India, there are various formal and informal ways in which a business can make a contribution towards CSR practices. CSR can be regarded as a way by which the companies are integrating their social, environmental and economic concerns into their values, culture, strategy, decision making and operations to improve the society and the society’s wealth. With deliberate and sincere efforts of the companies, they are attaining success in achieving their corporate goals in terms of social development, and are also able to enhance their corporate reputation. The ethical aspects related to CSR have become more apparent due to globalization and laws relating to social responsibilities and developments. For the present paper, the literature was examined on CSR and Corporate Sustainability. Nowadays, innumerous companies have been adopting CSR practices in order to attain corporate sustainability. The present research paper is confined to study various dimensions, features and the impact of CSR on the Indian corporate sector, i.e. Tata Consultancy Services (TCS), Coca - Cola India, BHEL and Wipro. The outcomes of the study show that the companies under study are following the CSR practices in many fields like education; community development; environmental protection; energy conservation; waste material management; health management; water management, etc. and are trying to encourage CSR awareness among different parts of the society.